Caracterización de la percepción del desempeño profesional a través del proceso de autoevaluación de la práctica temprana de los estudiantes de educación básica promoción 2005 de la Universidad de Playa Ancha (Educational Perspectives Magazine (REPED), 2022)
The following text is about self-assessment processes in the context of Early Practicum of the 2005 class of the Playa Ancha University Basic Education Pedagogy careen Self-assessment is recognized as a mean of specifying the reflexive processes described in the Professional Profile necessary for professional training. Some selfassessment description instruments for several stages of the Early Practicum (VISE) are analysed.
Keywords: Professional Profile, Early Practicum, reflexive and critical process, Self-Assessment.